High tech and high touch : The managerial perspective - Abdullah, Nor Azimah Chew; Yusof, Ab. Aziz (2008)
Technology revolution has made today’s organizations more challenging than yesterday. Technology has significantly affected almost every worker, both in the workplace and outside. The rapid and continuous speed of technology has changed the pattern of employment across the world. Now with technology, productivity enhancement, effectiveness improvement and competitive edge creation are possible. Thus, rapid technological changes have an impact on human resources. Hence, management of the information technology or also known as knowledge management is vital in determining the success or failure of organizations. As such, organizations are at the crossroad of either adapting the rapid technology or facing declining in organizational viability. Although the importance of knowledge has been recognized but alas organizations are unable to manage it as they neither understood the problems and opportunities nor strategies and solutions. Proactive adapting and designing the information technology is crucial, as accommodating information technology with organizational structure will create problems in the organizational culture. Roles of individual must be clearly defined to create successful interaction between high tech and soft touch of the twin. Nurturing the user-system interaction is critical as to have them talk the same language without confusion, misunderstanding and logical inconsistencies. As such, management will face three barriers that will affect the system in organization: autonomy, recognition and individualism. Therefore, top management has to use their power to ensure the designation of information is based on professional value like consistence, reliable, practical and flexible in order to avoid destructive conflict, feeling of alienation and evoking anger. Thus, marrying the technology with organizational structure will produce new knowledge that will enable the twin (high tech and soft touch) to be attached and not separated ever after.